When you reflect a function in the x-axis, the first coordinate of a point stays the same, and the second coordinate changes sign (what was positive is now negative and vice versa). See the attached picture.
Question 11: f(x) = -5x + 2. The function changes to its opposite, so g(x) = -(-5x + 2) = 5x - 2.
When you reflect a function in the y-axis, the first coordinate of a point changes to its opposite, but the second coordinate stays the same. Replace x with -x .
Question 14: f(x) = |2x - 1| + 3. Replacing x with -x produces g(x) = |2(-x) - 1| + 3 which simplifies to g(x) = |-2x -1| + 3.
Question 15 works the same way as #14.